THE RISE OF ISLAMIC RELIGIOUS-POLITICAL MOVEMENTS IN INDONESIA: The Background, Present Situation and Future (JOURNAL OF INDONESIAN ISLAM, 2008)
This paper traces the roots of the emergence of Islamic religious and political movements in Indonesia especially during and after their depoliticization during the New Order regime. There were two important impacts of the depoliticization, first, the emergence of various study groups and student organizations in university campuses. Second, the emergence of Islamic political parties after the fall of Suharto. In addition, political freedom after long oppression also helped create religious groups both radical on the one hand and liberal on the other. These radical and liberal groups were not only intellectual movements but also social and political in nature. Although the present confrontation between liberal and moderate Muslims could lead to serious conflict in the future, and would put the democratic atmosphere at risk, the role of the majority of the moderates remains decisive in determining the course of Islam and politics in Indonesia.